TRANSFORMATION OF MORAL VALUES IN FILM ADAPTATIONS OF CLASSIC ENGLISH NOVELS - Nur Innayah Ganjarjati (Education Studies and Teaching Journal (EDUTECH), 2025)
English classic novels have long been recognized as important sources of universal moral values. However, with the decline in the consumption of classical literature, film adaptations have emerged as a crucial medium for conveying these values ​​to contemporary audiences. This study examines the transformation of moral values ​​in film adaptations of English classic novels, identifying patterns of change (continuity, modification, and omission) and the factors influencing them. Using a multidisciplinary approach,narrative review and multidisciplinary analytical framework of adaptation theory, ethical criticism, and cultural studiesThis study finds that film adaptations often retain universal values ​, modify them to suit contemporary sensibilities, and eliminate or soften harsh social criticism. Factors such as historical and cultural context, audience reception, directorial ideology, and cinematic limitations play a significant role in this transformation process. This research contributes to adaptation studies by expanding the focus to the moral dimension and enriching ethical criticism by analyzing the ethical implications of film adaptations. The results of this study highlight the complexities of cultural reinterpretation and the ethical responsibilities of re-presenting classic narratives in the modern era.